PENGARUH BEBAN KERJA, IKLIM KERJA, STRES KERJA DAN AKTIVITAS FISIK TERHADAP PERILAKU PENCEGAHAN LBP (LOW BACK PAIN) PADA PERAWAT DI KAMAR OPERASI - Suryanto, Sugeng; Hafizzurrachman, M.; Rindu, Rindu (NHM PRESS, 2023)
Nurses working in operating rooms are at greater risk in terms of musculoskeletal problems because of pulling and pushing gurneys, beds and other equipment, transferring patients to operating tables or gurneys, supporting extremities for long periods of time and standing in the same position. for a long time. The purpose of this study was to determine the direct and indirect effects and the magnitude of workload, work climate, work stress and physical activity on LBP (Low Back Pain) prevention behavior in nurses in the Operating Room at M Hospital South Jakarta in 2022. The method used in this study is a quantitative approach using a cross- sectional design. The sample used was 100 pregnant women as respondents. The analytical method used was the Structural Equation Model (SEM) using SmartPLS 3.3 and SPSS 20. The results of hypothesis testing with the Structural Equation Model (SEM) with the smartPLS method found that the LBP prevention behavior variable was influenced by workload (29.12%), work stress ( 18.28%), work climate (14.45%) and physical activity (27.19). The direct effect of LBP prevention behavior was 89.0% and the indirect effect was 1.5 5% and the total direct and indirect effect was 90.6%. Workload is the dominant factor that greatly influences LBP prevention behavior. The higher the workload, the less good the LBP prevention behavior is for nurses and conversely the lower the workload, the better the LBP prevention behavior for nurses.